16‐5: Late‐News Paper: High Flux Stable Perovskite Quantum Dots‐Polymer Composite for Down‐Converting Applications. Issue 1 (25th September 2020) - Sinatra, Lutfan; Lutfullin, Marat; Lentijo-Mozo, Sergio; Bakr, Osman M.
Abstract : Perovskite Quantum Dots have excellent optical properties but low stability under high flux irradiation. In this work, a method to synthesize perovskite QDs‐polymer composite will be presented to overcome the high flux stability problem. As compared to pristine perovskite QDs, the perovskite QDs‐polymer composite shows higher stability under high flux condition in a long term.